Ethical Evidence and Policymaking Interdisciplinary and International Research - Iphofen, Ron; O'Mathúna, Dónal (Policy Press, 2022)
EPDF and EPUB available Open Access under CC-BY-NC-ND licence. This important book offers practical advice for using evidence and research in policymaking. The book has two aims. First, it builds a case for ethics and global values in research and knowledge exchange, and second, it examines specific policy areas and how evidence can guide practice. The book covers important policy areas including the GM debate, the environment, Black Lives Matter and COVID-19. Each chapter assesses the ethical challenges, the status of evidence in explaining or describing the issue and possible solutions to the problem. The book will enable policymakers and their advisors to seek evidence for their decisions from research that has been conducted ethically and with integrity.